Antithrombin: anti-inflammatory properties and clinical applications - Levy, Jerrold H.; Sniecinski, Roman M.; Welsby, Ian J.; Levi, Marcel (Thrombosis and Haemostasis, 2016)
Many humoral and cellular components participate in bidirectional communication between the coagulation and inflammation pathways. Natural anticoagulant proteins, including antithrombin (AT), tissue factor pathway inhibitor, and protein C, suppress proinflammatory mediators. Conversely, inflammation blunts anticoagulant activity and, when uncontrolled, promotes systemic inflammation-induced coagulation, such as those that occur in disseminated intravascular coagulation and severe sepsis. This review discusses the mechanisms of action and clinical use of AT concentrate in critically ill patients and in the settings of perioperative anticoagulation management for surgery and obstetrics. AT is a serine protease inhibitor with broad anticoagulant activity and potent anti-inflammatory properties. In clinical conditions associated with hereditary or acquired AT deficiency, administration of AT concentrate has been shown to restore proper haemostasis and attenuate inflammation. Of note, AT modulates inflammatory responses not only by inhibiting thrombin and other clotting factors that induce cytokine activity and leukocyte-endothelial cell interaction, but also by coagulation-independent effects, including direct interaction with cellular mediators of inflammation. An increasing body of evidence suggests that AT concentrate may be a potential therapeutic agent in certain clinical settings associated with inflammation. In addition to the well-known anticoagulation properties of AT for the treatment of hereditary AT deficiency, AT also possesses noteworthy anti-inflammatory properties that could be valuable in treating acquired AT deficiency, which often result in thrombotic states associated with an inflammatory component.
Keywords: Antithrombin; cardiac surgery; coagulation; disseminated intravascular coagulation; inflammation; pregnancy